2022
DOI: 10.3390/f13101684
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Endophytic Microbiota of Phytoplasma-Infected Russian Olive Trees “Elaeagnus angustifolia L.” in the Northwest of Iran

Abstract: In this study, Russian olive trees exhibiting witches’-broom symptoms were collected from urban green areas in Tabriz, in the northwest of Iran. PCR analysis confirmed that phytoplasma caused the disease and, according to the resulting Sanger sequencing electropherogram, a mixed infection with two or more phytoplasma species within the Russian olive trees was revealed. Next-generation sequencing analyses, using the Illumina method, were performed on total DNA from the infected Russian olive plants to recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The previously full genome of 'Ca. Phytoplasma asterisʼ was obtained as the causal agent of Russian olive witches'-broom disease in Iran [15]. However, in this research, in addition to 'Ca.…”
Section: Genomic Characterization Of Three Distinct Phytoplasma Speciesmentioning
confidence: 80%
See 2 more Smart Citations
“…The previously full genome of 'Ca. Phytoplasma asterisʼ was obtained as the causal agent of Russian olive witches'-broom disease in Iran [15]. However, in this research, in addition to 'Ca.…”
Section: Genomic Characterization Of Three Distinct Phytoplasma Speciesmentioning
confidence: 80%
“…In previous studies, the 'Ca. Phytoplasma asteris' was characterized as the causal agent of Russian olive witches 'broom disease in Iran [3,15]. However, MetaPhlAn2 analysis suggested that, in addition to 'Ca.…”
Section: Genomic Characterization Of Phytoplasmas With Russian Olive ...mentioning
confidence: 99%
See 1 more Smart Citation
“…To predict bacterial genomes and profile the composition of microbial communities, the MetaPhlAn2 pipeline version 2.6.6.17 was applied to the raw data. 17 , 18 …”
Section: Methodsmentioning
confidence: 99%
“…To predict bacterial genomes and profile the composition of microbial communities, the MetaPhlAn2 pipeline version 2.6.6.17 was applied to the raw data. 17,18 To assemble bacterial genomes, the raw data were mapped to the reference genomes that had been previously deposited in GenBank, using Bowtie2 software version 2.5.0. The mapped reads were then assembled by metaSPAdes software version 3.15.4.…”
Section: Next-generation Sequencing Analysesmentioning
confidence: 99%